Use of Blend Technique for Adjustment of Biodegradable Cellulose Acetate to Fiber Applications - Al-Dhafeer, Mona M.; Abdel-Naby, Abir S. (Asian Journal of Chemistry, 2017)
Cellulose acetate is a semi-ordered polymer, used in various plastic applications. To adjust this biodegradable polymer to fiber application, the polymer is blended through its amorphous matrix with acrylonitrile copolymers to thermally support the polymer. The blending process, assisted with ultrasonic waves, led to the formation of a homogeneous matrix up to 25 % of the copolymers content. A unique glass transition temperature indicates the formation of new macromolecular matrix as a result of each blend sample. The results revealed that the blend samples exhibited higher thermal stability as shown from thermal analysis as compared to cellulose acetate. The mechanical properties were also greatly improved. Thus, blending cellulose acetate with the prepared copolymers enable it to withstand high temperature, which adjust it for fiber applications.